Simplified seismic design procedure for steel MRF structure with nonlinear viscous dampers. (October 2021) - Dong, Baiping; Ricles, James M.
Abstract: This paper presents a simplified design procedure (SDP) for performance-based design of low-rise new steel MRF buildings with nonlinear viscous dampers. The SDP uses an effective stiffness and equivalent damping for a multi degree-of-freedom (MDOF) model of the MRF building, which is established using a linearized model of the damping system (damping devices and the associated bracing). The SDP is an integrated design process for the steel MRF and the damping system to achieve target performance objectives. The SDP is consistent with the analysis procedures in ASCE 7–16 for seismic design of conventional structures without dampers, however, differentiated from the analysis procedures for structures with dampers without the computation of effective period and effective damping ratio as a function of the ductility demand on the structure. The SDP was validated using nonlinear dynamic time history analyses (NDTHA) results for a 4-story example steel MRF building with nonlinear viscous dampers with two scenarios of damper arrangements in the building. The MRFs were designed for various base shear design strength levels (i.e., 100%, 75%, 60%, 50% and 40% of the required base shear design strength of ASCE 7–16), and nonlinear viscous dampers were sized and added to the MRFs to control the story drift response. The results presented in this paper show that performance objectives for the SDP can be selected and achieved using a MRF designed with smaller base shear design strength than a conventional MRF. Graphical abstract: Unlabelled Image Highlights: Developed performance-based integrated design procedure between seismic force-resisting system and damping system. Validated the accuracy of the new design procedure for seismic design of structures with nonlinear viscous dampers. Reduced base shear design strength up to 40% for MRFs with dampers for equivalent seismic performance of SMRF structures.